Potential economic impact of COVID-19-related school closures - Spencer Cohen; Sumathi Chakravarthy; Sindhu Bharathi; Badri Narayanan; Cyn-Young Park (Asian Development Bank (ADB), 2022)
Severe disruptions in school education during the coronavirus disease (COVID-19) pandemic has impacted children through their formative years which will affect their employment opportunities and earning potential for many years after school ages. This paper examines the medium-to-long-term economic scarring effects, using data available through the Global Trade Analysis Project, a computable general equilibrium model, with empirical study focusing on the impact of school closures on economic growth and employment. The estimated results show significant declines in global gross domestic product (GDP) and employment. Moreover, the losses in global GDP and employment increase over time. Declines in global GDP amount to 0.19% in 2024, 0.64% in 2028, and 1.11% in 2030. In absolute terms, the cost to the global economy in 2030 alone is 943 billion. The scarring effects are greater in economies with significant student populations from rural areas, those in the poorest and second wealth quintile. Learning and earning losses are also significant in economies where the share of unskilled labor employment in the overall labor force is high.
Keywords: I25; J24; P46; 330; school closure; labor productivity; economic growth; employment